A secure energy-efficient routing protocol for disease data transmission using IoMT. (July 2022) - Singh, Samayveer; Nandan, Aridaman Singh; Sikka, Geeta; Malik, Aruna; Vidyarthi, Ankit
Abstract: The outlook of the World toward health infrastructure has drastically changed due to COVID-19 which created the need for the development of emerging technologies where interactions between the patients and the health workers can be minimized. Consequently, a secure and energy-efficient internet of medical things (IoMT) enabled wireless sensor network (WSN) is proposed for communicable infectious diseases that utilizes genetic algorithm. The proposed system makes use of movable sinks in IoT-enabled WSNs for healthcare called OptiGeA. The OptiGeA protocol is depicted for cluster heads (CHs) election by joining the factor of energy, density, distance, and heterogeneous node's capacity for fitness function. Additionally, a novel deployment technique and multiple mobile sink approaches are proposed to reduce transmission distance between sink and CH during system operation which mitigates hotspot issues. It is evident from the simulations that the OptiGeA protocol outflanks state-of-the-art protocols in terms of different performance measurements.